2013
DOI: 10.1103/physrevb.88.224418
|View full text |Cite
|
Sign up to set email alerts
|

Random fieldxymodel in three dimensions

Abstract: We study random-field xy spin model at T = 0 numerically on lattices of up to 1000 × 1000 × 1000 spins with the accent on the weak random field. Our numerical method is physically equivalent to slow cooling in which the system is gradually losing the energy and relaxing to an energy minimum. The system shows glass properties, the resulting spin states depending strongly on the initial conditions. Random initial condition for the spins leads to the vortex glass (VG) state with short-range spin-spin correlations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 48 publications
3
61
0
1
Order By: Relevance
“…Стеклообразование в трехмерной XY-модели было предметом многочисленных исследо-ваний, основанных как на методах квантовой теории поля [5,6,4,7], так и на вычислительных методах, см., например, [14][15][16][17]. В частности, было промоделировано медленное охлаждение трехмерной XY-модели и проде-монстрировано, что система с первоначально случайно распределенными спинами замораживается в состоянии вихревого стекла [18]. Тем не менее, несмотря на значительные усилия, сам процесс стеклования и его связь с топологическими возбуждениями в XY-системах все еще остается малоизученным.…”
unclassified
“…Стеклообразование в трехмерной XY-модели было предметом многочисленных исследо-ваний, основанных как на методах квантовой теории поля [5,6,4,7], так и на вычислительных методах, см., например, [14][15][16][17]. В частности, было промоделировано медленное охлаждение трехмерной XY-модели и проде-монстрировано, что система с первоначально случайно распределенными спинами замораживается в состоянии вихревого стекла [18]. Тем не менее, несмотря на значительные усилия, сам процесс стеклования и его связь с топологическими возбуждениями в XY-системах все еще остается малоизученным.…”
unclassified
“…For the xy model (n = 2) in three dimensions the properties of that state have been studied in Ref. [3]. In this paper we focus on the comparative study of the F-state in a 3d xy model and in a 3d Heisenberg model (n = 3) with the goal to shed more light on the glassy properties of the RF system.…”
Section: Introductionmentioning
confidence: 99%
“…[42] In three dimensions strong non-equilbrium effects have been reported in Refs. [43,2,3]. Numerical studies of the 2d elastic media with pinning centers (that is similar to 2d xy model) [44] revealed that pinning creates dislocations and thus destroys the Bragg glass.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations